The effect of pre-operative information in relieving anxiety in oral surgery patients - Ng SKS, Chau AWL, Leung WK (Blackwell Synergy, 2004)
Appropriate stress management of patients is essential for smooth running of invasive or surgical dental procedures conducted under local anaesthesia.